Apuntes vinculados a la importancia de la implementación del Compliance penal - Missiego-del-Solar, Joaquín (2018)
From a time to be part the term “Compliance” has been strongly incorporated into the legal vocabulary, having acquired great importance that cannot pass in any way unnoticed nowadays, mainly in the business world. Not giving it importance will bring with it a series of contingencies, among which appear those of criminal nature, which will be the subject of this article. It is importance for legal entities to establish policies within them that allow them to develop their activities in full Compliance with current